Computer Simulations of Cancer Growth Using Cellular Automata. - Bugia,Niña Frances Therese V. (Philippine Computing Journal)
One-dimensional and two-dimensional cellular automata-based models are used to generate computer simulations of cancer growth dynamics. Results of computer simulations using Java show close agreement with the Gompertz's model of tumor growth and the CA model of in vitro carcinogenesis developed by Serra and villani.